Menumbuhkan Tanggung Jawab Sosial Melalui Pendidikan Kewarganegaraan Berbasis Nilai - Putri, Mas Fierna Janvierna Lusie; Astuti, Dini Yuli; Rahmat, Mutiara; Febriyanti, Nadila; Putri, Nur Awlia; Azizah, Zahrani Salwa (Universitas Cokroaminoto Yogyakarta, 2025)
This article is a literature review that discusses the role of value-based Civic Education in fostering social responsibility, focusing on theoretical foundations, teaching strategies, the role of teachers and curriculum, implementation challenges, and policy implications. The method used is a literature review, by analyzing relevant journal articles, books, and previous studies. The findings show that value-based Civic Education significantly influences the formation of students’ character to be religious, honest, caring, democratic, and socially aware. Effective teaching strategies include project-based learning, service learning, and civic engagement, which encourage students’ real involvement in society. However, implementation still faces challenges such as limited teacher training, exam oriented evaluation, resource inequality, and the influence of digital media. Therefore, strengthening action-based curricula, providing pedagogical training for teachers, building school-community partnerships, and developing authentic assessment instruments are required to achieve the objectives of Civic Education.